2022
DOI: 10.31557/apjcp.2022.23.5.1791
|View full text |Cite
|
Sign up to set email alerts
|

Global Incidence and Trend of Uveal Melanoma from 1943-2015: A Meta-Analysis

Abstract: Background: Uveal melanoma (UM) is the most common primary intraocular malignancy in adults arising from uveal tissue melanocytes. Considering limited population based studies, we performed a meta-analysis of uveal melanoma incidence rate in worldwide. Methods: For this meta-analysis, the electronic database of PubMed, Scopus, Embase and Google Scholar were utilized. Qualified Cohort studies and registry system databases were included in the study. Trend analysis and the estimation of incidences were reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The GNA11 Q209L missense mutation, giving rise to the FRMVDVGG L epitope, is the most frequent mutation in uveal melanoma (UM) (42,50% of all cases reported in TCGA). Unfortunately, the clinical impact of this neoantigen appears to be very limited because UM is a rare tumor, with an average incidence rate of 5 per million globally [ 19 ] and the binding B*27:05 and B*39:01 HLA alleles are among the least frequent in the World. The two big killers colon and stomach cancers show 18.8% and 23.9% of cases which are characterized by mutations giving rise to shared neoantigens and could benefit from cancer vaccines based on TSAs.…”
Section: Discussionmentioning
confidence: 99%
“…The GNA11 Q209L missense mutation, giving rise to the FRMVDVGG L epitope, is the most frequent mutation in uveal melanoma (UM) (42,50% of all cases reported in TCGA). Unfortunately, the clinical impact of this neoantigen appears to be very limited because UM is a rare tumor, with an average incidence rate of 5 per million globally [ 19 ] and the binding B*27:05 and B*39:01 HLA alleles are among the least frequent in the World. The two big killers colon and stomach cancers show 18.8% and 23.9% of cases which are characterized by mutations giving rise to shared neoantigens and could benefit from cancer vaccines based on TSAs.…”
Section: Discussionmentioning
confidence: 99%
“…Uveal melanoma (UM) is the most frequent primary malignant ocular tumour [ 1 , 2 ] and carries a substantial risk of visual impairment and mortality due to metastatic disease [ 3 ]. UM is a rare cancer, representing 3.2% of all melanoma cases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Uveal melanoma (UM) is the most common primary intraocular malignant tumour in adults, involving the iris, ciliary body or choroid, and is biologically distinct from cutaneous melanoma in terms of driver genes and mutational burden [1]. A meta-analysis of 22 studies published from 1943 to 2015 demonstrated an incidence rate of 5.74 (95% confidence interval [CI]: 4.37-7.11) and 7.30 (95% CI: 6.36-8.24) in the USA and Europe, respectively [2]. Nearly 50% of patients with UM develop metastatic disease within 15 years of their initial diagnosis.…”
Section: Introductionmentioning
confidence: 99%